2008
DOI: 10.1016/j.jinorgbio.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Combined QM/MM calculations of active-site vibrations in binding process of P450cam to putidaredoxin

Abstract: Combined QM/MM calculations of the active-site of cytochorme P450cam have been performed before and after the binding of P450cam to putidaredoxin. The calculations were carried out for both a 5-coordinated and a 6-coordinated active

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The geometric parameters in Figure 6 are in basic accord with the experimental data. 178 A recent DFT(B3LYP)/MM study of 3 with and without the reductase (putidaredoxin) by Freindorf et al 212 gave similar structural data and further showed that the Fe-S bond distance gets shorter upon binding of the reductase, to the proximal side of the active site. This bond shortening (by 0.05-0.10 Å) is accompanied by an increase of the stretching frequency of the Fe-S bond in qualitative accord with experimental findings.…”
Section: The Pentacoordinated Statesmentioning
confidence: 85%
“…The geometric parameters in Figure 6 are in basic accord with the experimental data. 178 A recent DFT(B3LYP)/MM study of 3 with and without the reductase (putidaredoxin) by Freindorf et al 212 gave similar structural data and further showed that the Fe-S bond distance gets shorter upon binding of the reductase, to the proximal side of the active site. This bond shortening (by 0.05-0.10 Å) is accompanied by an increase of the stretching frequency of the Fe-S bond in qualitative accord with experimental findings.…”
Section: The Pentacoordinated Statesmentioning
confidence: 85%
“…The modified PDB file was then loaded into xleap and recombined with the previously prepared heme and M-IV models using the 2Y98 coordinates for all atoms. A covalent linkage was created from the heme iron to Cys 346 with a Fe-S bond length of 2.45 angstroms (21). The water distally coordinated to the heme iron was retained based on evidence found in the 2Y98 (MycG-M-IV) and 2YGX (MycG) crystallographic structures.…”
Section: Methodsmentioning
confidence: 99%
“…A covalent linkage was created from the heme iron to Cys 346 with a Fe−S bond length of 2.45 Å. 21 The water distally coordinated to the heme iron was retained on the basis of evidence found in the 2Y98 (MycG−M-IV) and 2YGX (MycG) crystallographic structures. The complex was solvated within a cubic periodic box with 90 Å edges, leaving a minimal 15 Å distance from the periodic boundary to the protein surface.…”
mentioning
confidence: 99%
“…A covalent bond was created between the Fe atom at the coordination site of heme and the proximal cysteine, Cys 348, with a Fe-S distance of 2.45 Å, as computed by Freindorf et al33 using QM/MM. WAT 515 in the 3CPP structure (proposed to correspond to the K + bound between the B-B′ loop and B′ helix) was replaced with a potassium ion 34.…”
Section: Methodsmentioning
confidence: 99%